2017
DOI: 10.3892/mmr.2017.8274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key pathways and genes in Barrett's esophagus using integrated bioinformatics methods

Abstract: Barrett's esophagus (BE) is a premalignant lesion of esophageal adenocarcinoma. The aim of the present study was to investigate the possible mechanisms and biomarkers of BE. To identify the differentially expressed microRNAs (DEmiRNAs) and genes (DEGs) in BE, the miRNA expression profile GSE20099 and the gene expression profiles GSE26886, GSE13083 and GSE34619 were obtained from the Gene Expression Omnibus (GEO) database. DEGs and DEmiRNAs were screened for using the GEO2R tool. Using DAVID, functional and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As a common complication of GERD, the incidence of BE is rapidly increasing 3 . Therefore , it can be confirmed is that the overall prevalence of BE is increasing 5 . However, the molecular mechanism of BE is still unclear.…”
Section: Introductionmentioning
confidence: 83%
“…As a common complication of GERD, the incidence of BE is rapidly increasing 3 . Therefore , it can be confirmed is that the overall prevalence of BE is increasing 5 . However, the molecular mechanism of BE is still unclear.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, patients with CF have higher rates of delayed gastric emptying (up to 33%) and increased duodenogastro-esophageal reflux, which may contribute to more severe GERD[ 30 ]. Prolonged exposure of the esophageal mucosa to both stomach acid and bile acid may result in a premalignant lesion to EAC, known as Barrett’s esophagus (BE)[ 29 , 31 , 32 ]. Multiple studies have shown an increased risk for BE with CF[ 33 ], especially after liver transplantation[ 29 , 34 ].…”
Section: Rationale For Screening Of Gi and Hepatopancreatobiliary Cancersmentioning
confidence: 99%